2021
DOI: 10.18176/archmeddeporte.00033
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the anthropometric profile and physical fitness of surfers and their dynamic postural balance

Abstract: Introduction: Surfing is a discipline that has considerably increased the number of followers who practice this sport. Research has focused on describing the main variables associated with performance, but not the relationships that may exist between them. Objective: To establish the relationship of dynamic postural balance with respect to the anthropometric profile and physical aptitude in surfers. Material and method: This research is an observational and cross-sectional study of a descriptive-correlational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…For their part, the endomorph and ectomorph somatotypes influence the performance of the anterior reach of the dynamic postural balance in a negative and positive way, respectively. These results agree with those reported in other athletes, where it has been seen that variables related to the accumulation of adipose tissue, such as body mass index and percentage of body fat, have been negatively associated with the performance of postural balance (Hartley, Hoch, & Boling, 2018;Morales-Vargas et al, 2021). Specifically, young basketball players have observed that a higher percentage of fat mass is related to poor postural balance (Kostopoulos, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…For their part, the endomorph and ectomorph somatotypes influence the performance of the anterior reach of the dynamic postural balance in a negative and positive way, respectively. These results agree with those reported in other athletes, where it has been seen that variables related to the accumulation of adipose tissue, such as body mass index and percentage of body fat, have been negatively associated with the performance of postural balance (Hartley, Hoch, & Boling, 2018;Morales-Vargas et al, 2021). Specifically, young basketball players have observed that a higher percentage of fat mass is related to poor postural balance (Kostopoulos, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, it was found hat variables related to the accumulation of adiposity such as the percentage of fat mass and endomorphy negatively influence the dynamic postural balance. It has been proposed that the accumulation of fatty tissue around and within the muscle could alter the standard mechanisms of motor responses due to physiological and neuromuscular changes (Morales-Vargas et al, 2021;Pajoutan, Ghesmaty Sangachin, & Cavuoto, 2017). The accumulation of fat would increase the expression of proinflammatory cytokines in the muscle, which could reduce the electrochemical balance and neural conductivity (Addison et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The suggestion that functional movement skills could be associated with Parkour performance has to some extent been investigated by Abellan‐Aynés and Alacid (2016) who separated Traceurs into high and low performance groups based on judges’ scores. The high‐performance group significantly outperformed their counterparts in both counter movement and long jump tasks, suggesting that performance on these tests of functional movement skill is associated with Parkour performance.…”
Section: Introductionmentioning
confidence: 99%